Customers Buying Behaviour on Branded Apparels - Sharma, B; Hyde, A.M; Tharani, M (International Journal of Computer Sciences and Engineering, 2025)
The opening up of branded apparel outlets, shopping malls are increasing all over the country. The change in the lifestyle of the Indian consumers, rise in the working class, increase in disposable incomes, dual career families, fast urbanization, education, media and information, and many other economic and social changes offer a wide range of opportunities, and contribute in accelerating the pace of growth in the business. The apparel retailing in India consists of 95 percentages of total sales in department stores, 70 percentage in hypermarkets such as Big Bazaar, Spencer’s Retail etc. The apparel fashion retail brands have been uplifting the business and economy in India very fast. The apparel industry is one of the extreme significant sectors of the India in terms of generating revenue, investment, and trade and job creation. Apparel industry has remarkable product variety, short product life cycles, volatile and changeable demand, long and stiff distribution network. Transitional shift can be seen in the apparel industry with time. The enhanced demand of branded apparel is driving retailers to plan stand-alone stores. Therefore, focus of the research was to study buying behavior of customers towards branded clothes. For the study sample of 130 respondents were considered and factor analysis was applied on primary collected data. In the study, based on primary data six factors were identified towards buy behavior of branded clothes i.e. Affordability, Brand Loyalty, Reliability, Quality and Status